PELAKSANAAN TUGAS DAN FUNGSI BADAN PERTANAHAN NASIONAL KABUPATEN KUPANG DALAM PROSES PENGADAAN SERTIFIKAT TANAH BAGI MASYARAKAT EKS TIMOR TIMUR DI DESA TUAPUKAN KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Ferlindo Dominggus Mascareinhas; Saryono Yohanes; Megi Octaviana Radji; Hernimus Ratu Udju (PT. Saha Kreasi Indonesia, 2026)
This study aims to examine the implementation of the duties and functions of the National Land Agency (Badan Pertanahan Nasional/BPN) of Kupang Regency in the process of land certificate issuance for former East Timor communities in Tuapukan Village, East Kupang District, Kupang Regency, as well as to identify the factors that hinder its implementation. The background of this research is based on the ongoing land-related problems faced by former East Timor communities who have chosen Indonesian citizenship, particularly regarding legal certainty over land ownership. Land certification is a crucial instrument to ensure legal certainty, improve economic welfare, and support the social integration of former refugees. This research employs a normative legal research method with a juridical approach, focusing on the analysis of land-related laws and regulations, particularly Law Number 5 of 1960 on Basic Agrarian Principles, Government Regulation Number 24 of 1997 on Land Registration, and other relevant regulations. The findings indicate that the BPN of Kupang Regency has carried out its duties and functions in land certificate issuance through land registration procedures, measurement and mapping, collection of physical and juridical data, and issuance of land title certificates. However, several obstacles remain, including the lack of integrated commitment between central and local governments, limited technical support and professional capacity of human resources, low community participation, incomplete land ownership documents, and unclear legal status of disputed lands. These constraints have resulted in suboptimal legal certainty over land ownership for former East Timor communities in Tuapukan Village. This study concludes that strengthening inter-agency coordination, enhancing institutional capacity of the National Land Agency, and increasing public awareness and participation are essential to improve the effectiveness of land certification for former East Timor communities in order to ensure legal certainty and agrarian justice.